FAKTOR RISIKO INFEKSI PADA ANAK 1-2 TH - KUSUMASTUTI, ARYU CANDRA (JNH (Journal of Nutrition and Health), 2014)
Background Infectious diseases, especially respiratory and gastrointestinal infections are the leading cause of death in children in developing countries, including Indonesia . Risk factors for infection can be categorized into external factors (eg environment) and internal factors (eg nutrition status and immunity status). Objective This study aimed to explore the risk factors of infection in children 1-2 years old with hope can help reduce the incidence of infectious diseases in Indonesia. Methods This study is a case-control study with a sample of 46 for each group of cases and controls. The study was conducted in Semarang city in 2011. Dependent variable was the incidence of infection in children 1-2 years old while the independent variable are the level of mother's education, father's education level, economic status of the family, father smoking status, a history of low birth weight, immunization history, nutritional status, history of exclusive breastfeeding, and complementary feeding. Data analysis was performed using univariate, bivariate by chi-square test, and multivariate by multiple logistic regression. Results Multivariate analysis showed that the variables proved to be a risk factor for infection is nutritional status (p: 0.011; OR: 3.34; :1,28 CI-8, 75), Complementary feeding (p: 0.009; OR: 3.6; :1,32 CI-9, 73), and the father smoking status (p: 3.34, OR: 3.34, CI :1,28-8, 75). Variables not significantly associated with the incidence of infection is sex, birth weight, immunization history, history of breastfeeding, economic status, mother's education level and father's education level. Conclusions Nutritional status, history of complementary feeding, and father smoking status is a risk factor for infectious diseases in children 1-2 years old. Keywords: infection, infectious disease, risk factors, children ABSTRAK Latar Belakang Penyakit infeksi terutama infeksi pernafasan dan pencernaan merupakan penyebab kematian terbesar pada anak di negara berkembang termasuk Indonesia..Faktor risiko infeksi dapat dikategorikan menjadi faktor eksternal (lingkungan) dan faktor internal Penelitian ini bertujuan untuk mencari faktor risiko infeksi pada anak 1-2 th dengan harapan dapat membantu menurunkan angka kejadian penyakit infeksi di Indonesia. Metode Penelitian ini merupakan penelitian kasus kontrol dengan jumlah sampel 46 untuk masing-masing kelompok kasus dan kontrol. Penelitian dilakukan di kota Semarang pada tahun 2011. Variable terikat adalah kejadian infeksi pada anak 1-2 th sedangkan variable bebas adalah  tingkat pendidikan ibu, tingkat pendidikan ayah, status ekonomi keluarga, status perokok ayah, riwayat berat badan lahir rendah, riwayat imunisasi, status gizi, riwayat Air Susu Ibu (ASI) eksklusif, dan Makanan Pendamping (MP) ASI. Analisis data dilakukan secara univariat, bivariat dengan chi square, dan multivariate dengan uji regresi logistic berganda Hasil Hasil analisis multivariat menunjukkan variabel yang terbukti sebagai faktor risiko infeksi adalah status gizi (p:0,011; OR:3,34; CI:1,28-8,75),  Makanan Pendamping ASI (p:0,009; OR:3,6; CI:1,32-9,73), dan status perokok ayah (p:3,34, OR: 3,34, CI:1,28-8,75). Variabel yang berhubungan tidak bermakna dengan kejadian infeksi adalah jenis kelamin, berat lahir, riwayat imunisasi, riwayat ASI eksklusif, status ekonomi, tingkat pendidikan ibu dan tingkat pendidikan ayah. Simpulan Status gizi, riwayat Makanan Pendamping ASI, dan status perokok ayah merupakan faktor risiko infeksi pada anak 1-2 th. Kata kunci: infeksi, factor risiko, anak, malnutrisi